Urban logistics and its development to the present (Business Vision, 2019)
This paper presents the literary review from the emergence of urban logistics to its development and conceptual evolution, which go hand in hand with the optimization of all processes that involve the movement of goods in a local environment. The public policies that must be followed and the evaluation systems implemented to measure the efficiency with which they carry out local replenishment in cities that have a high population density and a high demand for goods necessary to survive, are of vital importance for the search of solutions with the purpose of reducing the "bottlenecks" generated during the urban distribution of merchandise and streamline this process, from its origin going back to the eighties, a time in which the urbanization of the cities provokes a revolution in how to conduct business operations within cities. What characterizes this time is the deficiency in infrastructure, that is, the roads are not of quality so that the products reach all the sectors of a city, but from the development of the cities it is also accelerated, due to the expansion of the vehicle fleet, the number of vehicles that appear in the cities generates the need to expand the roads, in addition the urbanizations need to connect with each other by roads, which requires a kind of zoning to optimize the process of delivery of products within the cities. The generation of new roads also requires companies to plan their delivery routes that speed up and optimize their costs and processes. Currently the most developed cities can be noted a quality infrastructure consisting of specific areas for loading and unloading, established routes, hours of service, and a number of methods that have emerged and have been implemented over time.
Keywords: urban logistics; efficiency; mobility